Analisis Peran Diskon Barang Dalam Meningkatkan Efektivitas Pemasaran dan Kemajuan Usaha di Era E-Commerce: Penelitian - Irin Mirrah Luthfia; Bagus Yunianto Wibowo; Nanang Adie Setyawan; Destine Fajar Wiedayanti; Mona Inayah Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of digital technology has driven the growth of e-commerce as a major platform in modern trade activities. In increasingly competitive conditions, businesses are required to implement effective marketing strategies, one of which is through product discounts. This study aims to analyze the role of product discounts in increasing marketing effectiveness and their contribution to business progress in the e-commerce era. This study uses a quantitative approach with a descriptive associative method. Data were collected through questionnaires distributed to 120 active e-commerce businesses that have used discount strategies. The analysis techniques used include validity and reliability tests, multiple regression, and the Sobel test to examine the mediation effect. The results show that product discounts have a significant effect on marketing effectiveness (β = 0.568; p < 0.01), and marketing effectiveness has a significant effect on business progress (β = 0.612; p < 0.01). Discounts also have a direct effect on business progress (β = 0.325; p < 0.05), but the indirect effect through marketing effectiveness is proven to be stronger based on the results of the Sobel test (Z = 3.85; p < 0.001). This finding provides important implications for e-commerce business actors to be able to utilize discounts appropriately in building their business progress.